The yellow wallpaper and other stories eaudiobook - Gilman, Charlotte Perkins (Tantor Media, 2011)
This collection brings together twelve of the finest short stories of prominent American feminist author Charlotte Perkins Gilman. "The Yellow Wallpaper," Gilman's best-known work, was first published in 1892 and represents an important examination of nineteenth-century attitudes toward women's physical and mental health. Written as a collection of journal entries by a woman whose physician husband has confined her to her bedroom, the story depicts the narrator's descent into psychosis as her confinement gradually erodes her sanity. This collection also includes the stories "The Giant Wistaria," "According to Solomon," "The Boys and the Butter," "Her Housekeeper," "Martha's Mother," "A Middle-Sized Artist," "An Offender," "When I Was a Witch," "The Cottagette," "Making a Living," and "Mr. Robert Grey Sr."